Influência da elevaçáo transitória e da elevaçáo sustentada da pressáo arterial sobre a primeira derivada temporal da pressáo ventricular. - Bregagnollo, E. A.; Matsubara, B. B.; Padovani, C.; Tucci, P. J. (My University, 1992)
PURPOSE--To analyze the influence of transient and sustained elevations of arterial pressure (AP) on the rate of rise of the left ventricular pressure (dp/dt). METHODS--Thirteen anesthetized, thoracotomized and mechanically ventilated dogs, submitted to pharmacological autonomic block (oxprenolol-3 mg/kg plus atropine-0.5 mg/kg). The AP elevation was obtained by mechanical constriction of the descending thoracic aorta. Two protocols were applied to all animals: Transient Arterial Hypertension (TAH) and Sustained Arterial Hypertension (SAH) and the following variables were evaluated: heart rate (HR), systolic (LVSP) and end diastolic (LVEDP) left ventricular pressure and dp/dt. In TAH the variables were analyzed in the basal condition (To) and at the maximal value of AP attained during the transient pressure elevation (TM). In the protocol SAH the variables were evaluated in the conditions: Control (Ho), hypertension 1 (H1) and hypertension 2 (H2). RESULTS--Considering all conditions, there were no significant differences among the values of HR. In the protocol TAH, the LVSP varied from 133 +/- 22 mmHg to 180 +/- 27 mmHg, whereas in SAH the values of LVSP were as follow: HO = 129 +/- 25 mmHg; H1 = 152 = 23 mmHg; H2 = 182 +/- 24 mmHg. LVEDP changed in both protocols: To = 7 +/- 2 mmHg; TM = 13 +/- 2 mmHg (p < 0.05); Ho = 7 +/- 2 mmHg; H1 = 10 +/- 2 mmHg; H2 = 14 +/- 3 mmHg (p < 0.05). During TAH there was no difference between the values of dp/dt (To = 3.303 +/- 598 mmHg/s; TM = 3.350 +/- 653 mmHg/s; p > 0.05), however, there were increases of the dp/dt during SAH (Ho = 3.233 +/- 576 mmHg/s; H1 = 3.831 +/- 667 mmHg/s; H1 = 4.594 +/- 833 mmHg/2; p < 0.05). CONCLUSION--The values of dp/dt are not influenced by transient elevation of AP. Sustained increase of AP activates cardiac adjustments, which results in elevation of dp/dt, by stimulation of contractile state. Probably, the inotropic intervention mechanism is the length dependent activation due to the Frank-Starling mechanism.
Influence of transient and sustained increase of blood pressure on the 1st temporal derivative of the ventricular pressure
Keywords: animal; blood pressure; dog; heart catheterization; heart contraction; heart left ventricle function; heart rate; hypertension; male; pathophysiology; physiology; review; Animal; Blood Pressure; Dogs; English Abstract; Heart Catheterization; Heart Rate; Hypertension; Male; Myocardial Contraction; Ventricular Function, Left